Traumatic memory in Chigozie Obioma’s The Fishermen and Vaddey Ratner’s in the Shadow of the Banyan - Al Mubarak, Ahmed Dhakaa Abdulwahhab (2019)
Most research in the field of trauma studies has been limited to particular forms of traumatic memory like flashback, or traumatic nightmare or cultural artifacts, but my research will strive to focus on a new form of traumatic memory resulting from transference phenomena. Through this new form, the traumatized characters develop a new understanding in the present about what happened in the past. As a result, the characters become able to sense the survival function of trauma. Also, this form of traumatic memory provides authors with the ability to examine how their characters retrieve traumatic memories into narrative form. Some researchers have examined traumas of the fictional characters as a colonial manifestation of gender, slavery and race in the light of postcolonial, identity, historical, and feminist theories. I intend to fill the gap by examining contemporary African and Cambodian literature produced by traumatized African and Cambodian authors in the light of Cathy Caruth’s trauma theory and Dori Laub’s concepts of traumatic memory. This thesis conducts a close analysis of characters’ traumatic memory resulting from or affected by the Nigerian and Cambodian civil wars in the fictional works of Chigozie Obioma’s The Fishermen (2015) and Vaddey Ratner’s In the Shadow of the Banyan (2012). I construct a theoretical framework by examining debates about the traumatic memory and narrative that have taken place in the fields of trauma studies and literary fiction. By drawing these debates, I argue that the traumatized victim is able to retrieve the unintegrated fragments of the literal registration in the black hole trauma by projecting them through transference phenomena onto currently experienced objects and relations. Consequently, these traumatic memories can also expose the enigma of trauma as not only a reason of psychological destruction, but also a reason for survival. The study aims to identify the literal registration of the traumatic events and the black hole effects in the selected novels. The characters enter into silence of the black hole, which becomes a source of pain and fear. I aim to explore the ways in which the novels present transference phenomena and their counter-intuitive roles in re-externalising traumatic events that happened in the past, then grafting those events onto situations in the present. This research will analyse the effects of the transference phenomena on the survival function of trauma and whether the main characters manage to overcome the heavy burden of their traumatic memories. The findings from the research show that the selected characters went through ‘the literal registration’ of the traumatic event and the black hole effect of their traumatic memory. Therefore, traumatic memory belatedly returning through transference phenomena plays its role as a coping mechanism for survival. This study aims to enlighten readers on how both Obioma and Ratner bring a victim to speak what had not been spoken before, as well as bring into being a witness as a narrator of the atrocities of war through transference phenomena in fiction.